Karen Kramer, Curator of Native American and Oceanic Art and Culture and Director of the Native American Fellowship Program, Peabody Essex Museum - Karen Kramer (Panorama, 2018)

(untitled)
Centering on T.C. Cannon as narrator of the exhibition, and decentralizing my curatorial voice as the authority, was an intentional strategy I employed to activate Cannon’s Native perspective and to build empathy with the audience.